Biological function derived from predicted structures in CASP11. (15th June 2016) - Huwe, Peter J.; Xu, Qifang; Shapovalov, Maxim V.; Modi, Vivek; Andrake, Mark D.; Dunbrack, Roland L.
ABSTRACT: In CASP11, the organizers sought to bring the biological inferences from predicted structures to the fore. To accomplish this, we assessed the models for their ability to perform quantifiable tasks related to biological function. First, for 10 targets that were probable homodimers, we measured the accuracy of docking the models into homodimers as a function of GDT‐TS of the monomers, which produced characteristic L‐shaped plots. At low GDT‐TS, none of the models could be docked correctly as homodimers. Above GDT‐TS of ∼60%, some models formed correct homodimers in one of the largest docked clusters, while many other models at the same values of GDT‐TS did not. Docking was more successful when many of the templates shared the same homodimer. Second, we docked a ligand from an experimental structure into each of the models of one of the targets. Docking to the models with two different programs produced poor ligand RMSDs with the experimental structure. Measures that evaluated similarity of contacts were reasonable for some of the models, although there was not a significant correlation with model accuracy. Finally, we assessed whether models would be useful in predicting the phenotypes of missense mutations in three human targets by comparing features calculated from the models with those calculated from the experimental structures. The models were successful in reproducing accessible surface areas but there was little correlation of model accuracy with calculation of FoldX evaluation of the change in free energy between the wild‐type and the mutant. Proteins 2016; 84(Suppl 1):370–391. © 2016 Wiley Periodicals, Inc.